Effect of Al–5Ti–1B on grain refinement, dendrite coherency and porosity of AZ91E magnesium alloy. (February 2015) - Vlasceanu, M.; Lun Sin, S.; Elsayed, A.; Ravindran, C.
<x content-type="archive" xml:space="preserve">Abstract</x> The dendrite coherency point is an important characteristic governing the castability of an alloy. In this study, the effect of Al–5Ti–1B additions on the grain size and dendrite coherency point of AZ91E magnesium alloy was investigated. It was observed that additions of 0·005 wt-%Ti led to a decrease in the grain size and the porosity level of AZ91E. This was accompanied by a significant increase in the coherency fraction of solid. However, with further additions of titanium up to 0·30 wt-%, the grain size increased and the coherency fraction of solid decreased. This was ascribed to increased growth rate, resulting from a change in the dendritic morphology from equiaxed to a lancet structure.